Long-term follow-up in PMM2-CDG: are we ready to start treatment trials? - Witters, Peter; Honzik, Tomas; Bauchart, Eric; Altassan, Ruqaiah; Pascreau, Tiffany; Bruneel, Arnaud; Vuillaumier, Sandrine; Seta, Nathalie; Borgel, Delphine; Matthijs, Gert; Jaeken, Jaak; Meersseman, Wouter; et al. (Genetics in medicine, 2019)
PURPOSE: PMM2-CDG is the most common congenital disorder of glycosylation (CDG), which presents with either a neurologic or multisystem phenotype. Little is known about the longitudinal evolution. METHODS: We performed data analysis on PMM2-CDG patients' clinical features according to the Nijmegen CDG severity score and laboratory data. Seventy-five patients (28 males) were followed up from 11.0 ± 6.91 years for an average of 7.4 ± 4.5 years. RESULTS: On a group level, there was no significant evolution in overall clinical severity. There was some improvement in mobility and communication, liver and endocrine function, and strabismus and eye movements. Educational achievement and thyroid function worsened in some patients. Overall, the current clinical function, the system-specific involvement, and the current clinical assessment remained unchanged. On follow-up there was improvement of biochemical variables with (near) normalization of activated partial thromboplastin time (aPTT), factor XI, protein C, antithrombin, thyroid stimulating hormone, and liver transaminases. CONCLUSION: PMM2-CDG patients show a spontaneous biochemical improvement and stable clinical course based on the Nijmegen CDG severity score. This information is crucial for the definition of endpoints in clinical trials.
Keywords: vrozené poruchy glykosylace; Phosphotransferases (Phosphomutases); Humans; dítě; Disease Progression; Child; následné studie; Female; mladý dospělý; Phenotype; lidé; fosfotransferasy (fosfomutasy); předškolní dítě; Congenital Disorders of Glycosylation; ženské pohlaví; Male; fenotyp; Adolescent; Young Adult; progrese nemoci; mužské pohlaví; Child, Preschool; Follow-Up Studies; mladiství